Pengaruh Struktur Modal, Profitabilitas, Ukuran Perusahaan, dan Kepemilikan Manajerial Terhadap Nilai Perusahaan pada Perusahaan Manufaktur yang Terdaftar di BEI - Endah Nurcahyati; Syarif M. Helmi; Rusliyawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of capital structure, profitability, company size, and managerial ownership on company value, especially in companies included in the automotive sub-sector listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2023. Company value is an important aspect because it reflects the company's performance and future prospects, as well as being the basis for strategic decision making. Internal factors such as capital structure, level of profitability, company scale, and management ownership are believed to play a role in company value. However, the findings of previous studies still show inconsistencies, especially in the automotive sub-sector after the COVID-19 pandemic. This study uses a quantitative approach with secondary data obtained from the Indonesia Stock Exchange (IDX), in the form of financial reports and annual reports of automotive companies during the study period. The sample was selected using a purposive sampling technique based on certain criteria, so that 55 observation data were obtained. Data analysis was carried out through descriptive statistical tests, classical assumption testing, multiple linear regression, and hypothesis testing. The results of this study indicate that capital structure and profitability have a negative effect on company value, while company size and managerial ownership do not have a significant effect on company value.